Growth and Yield Response of Kailan Plants (Brassica Oleraceae L.) to Various Doses of Guano Fertilizer - Firmansyah, Efrin; Shafanah, Aniq Humaira; Hidayat, Cecep (ISTEK, 2025)
Kailan is a vegetable plant from the cabbage family that has promising potential due to its high economic value and the high nutritional content contained in kailan. However, kailan production is still unstable due to the continuous use of inorganic fertilizers, resulting in a decrease in soil quality in terms of physical, chemical, and biological properties. Actions that can be taken to stabilize kailan production can be done by adding organic guano fertilizer to kailan plant cultivation. The purpose of this study was to determine the effect of various doses of guano fertilizer on the growth and yield of kailan plants (Brassica oleraceae L.). The method used in this study was a randomized block design (RAK) with 5 treatments and 5 replications, namely A: Control, B: 5 tons ha-1, C: 10 tons ha-1, D: 15 tons ha-1, and E: 20 tons ha-1. The results showed that the administration of various doses of guano fertilizer affected the parameters of plant height 35 HST, number of leaves 35 HST, leaf size, leaf area, and fresh weight of plants. However, it did not affect the harvest index parameters. In treatment D, the application of guano fertilizer dose of 15 tons ha-1 was able to provide the best results for the growth and yield of kale plants in the parameters of plant height 35 HST, number of leaves 35 HST, leaf size, leaf area, fresh weight of plants, and dry weight of plants. Therefore, the dose of 15 tons ha-1 is the recommended dose for kale plant cultivation.